Report & accounts of Bangladesh Rehabilitation Assistance Committee for the period from February 1 to December 31, 1974 - BRAC (© BRAC, 2016)
This Financial Statement prepared by S.F. Ahmed & Co. Chartered Accountants, 95 Motijheel, Dacca-2, Bangladesh.